The Influence of Work Motivation, Career Development, and Organizational Culture on Employee Job Satisfaction at PT. BDI - Ndoloe, Amasa Esaf Hendrikus; Napitupulu, Elfrida Viesta (CV. Publikasi Indonesia, 2024)
The research investigates the factors contributing to employee job satisfaction at PT BDI, where a survey in 2022 revealed that 57% of employees were dissatisfied, highlighting issues in work motivation, career development, and organizational culture. The purpose of this research is to determine the effect of work motivation, career development and organizational culture on PT BDI employee job satisfaction. The research method is a quantitative research method where obtained sample are 67 PT BDI employees. The sampling technique is based on saturated sampling using the questionnaire method. The analysis method uses Multiple Regression Analysis with the SPSS version 22 program. The conclusion of this study is that Work Motivation have a positive and significant effect on Job Satisfaction, Organizational Culture have a positive and significant effect on Job Satisfaction, meanwhile Career Development has a positive but not significant effect on PT BDI employee Job Satisfaction.